2012
DOI: 10.1073/pnas.1113342109
|View full text |Cite
|
Sign up to set email alerts
|

Impact of cross-protective vaccines on epidemiological and evolutionary dynamics of influenza

Abstract: Large-scale immunization has profoundly impacted control of many infectious diseases such as measles and smallpox because of the ability of vaccination campaigns to maintain long-term herd immunity and, hence, indirect protection of the unvaccinated. In the case of human influenza, such potential benefits of mass vaccination have so far proved elusive. The central difficulty is a considerable viral capacity for immune escape; new pandemic variants, as well as viral escape mutants in seasonal influenza, comprom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
77
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(79 citation statements)
references
References 34 publications
2
77
0
Order By: Relevance
“…Universal vaccines that immunize against all strains necessarily slow antigenic evolution by not discriminating between antigenic variants [12]. However, despite the fact that conventional vaccines create selective gradients among antigenic variants, our results suggest that conventional vaccines still reduce evolution and drive extinction.…”
Section: Discussionmentioning
confidence: 48%
See 2 more Smart Citations
“…Universal vaccines that immunize against all strains necessarily slow antigenic evolution by not discriminating between antigenic variants [12]. However, despite the fact that conventional vaccines create selective gradients among antigenic variants, our results suggest that conventional vaccines still reduce evolution and drive extinction.…”
Section: Discussionmentioning
confidence: 48%
“…Universal vaccines, which confer immunity against all antigenic variants, slow antigenic evolution by uniformly decreasing the fitness of all strains [12]. Conventional vaccines against seasonal influenza, which confer narrower immunity, might also slow antigenic evolution.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For our parameterization, this calculation indicates that the benefit of vaccination extends beyond simply decreasing the number of currently infected hosts; vaccination has the additional effect of reducing the rate of antigenic evolution. This result is echoed in a recent study that found that a broad-spectrum influenza vaccine could potentially decrease the rate of antigenic evolution as well as decrease disease incidence (Arinaminpathy et al 2012). Because peaks in incidence occur in years with strain turnover ( fig.…”
Section: Implications Of Eco-evolutionary Dynamics For Population Consupporting
confidence: 56%
“…Thus, annual vaccine reformulation is necessary to ultimately maintain immunity against seasonal influenza viruses [4,5]. Furthermore, antigenic drift renders uniform population wide vaccination campaigns, that have led to the control of measles and smallpox, ineffective for influenza virus [6]. Clearly, there is a great need for a vaccine that induces heterosubtypic protection against all influenza A viruses.…”
Section: Introductionmentioning
confidence: 99%